(untitled) (Medicine Today, 2025)
Introduction with Objective: The aim of the present study was to evaluate the Outcome of Gartland Type III Paediatric Supracondylar Humerus Fracture Fixation with the Kapandji Technique in the Prone Position. Materials and Methods: This prospective study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chittagong within the defined period from January 2020 to February 2022. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. The results were expressed as percentage and mean ± SD and p<0.05 was considered as the level of significant. Result: Out of 30 patients, the mean ± SD age of the patients was 7.7 ± 2.2 years. Most of the patients (56.7%) belonged to male. Out of 30 patients, Most of the (n=13, 43.3%) patients time from injury to procedure was 5 days. Mean ± SD time from injury to procedure was 4.77 ± 1.331 (range: 3-7) days. Majority of the (n=12, 40%) patients needed 30 minutes for operation from manipulation to casting. Mean ± SD time of procedure was 30.5 ± 5.309 (range: 20-40) minutes. After 1st week follow-up, all the 30 (100%) patients’ outcome was poor; after 4th week follow-up, 27 (90%) patients had fair and 3 (10%) patients had poor outcome and after 18th week final follow-up, excellent outcome was in 27 (90%) patients and good outcome was in 03 (10%) patients. Conclusion: After analyzing the Results of present study, it can be concluded that management of Gartland type III supracondylar humerus fractures in children using the Kapandji technique in the prone position is a feasible and safe method. So, it could be an alternative technique. Medicine Today 2025, Vol.37 (1): 33-36